2020
DOI: 10.1002/cctc.202001163
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Catalytic Applications of Nanosized High‐Entropy Alloys

Abstract: Creative approaches towards the fabrication of metal nanomaterials for catalysis are highly demanded. In this context, integrating multiple elements into single nanosized alloys opens up a new route for tailoring catalytic performance. Particularly, nanosized high‐entropy alloys (HEAs) with five or more metallic components have emerged as a new platform for catalyst discovery in broad cases, such as ammonia decomposition, ammonia oxidation, and various electrochemical reactions. In this minireview, the vigorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 109 publications
(124 reference statements)
0
27
0
Order By: Relevance
“…Several recent papers have reviewed the catalytic applications mainly based on high-entropy alloys (HEAs), while entropy-stabilized systems beyond HEAs have been rarely covered (10)(11)(12)(13)(14)(15)(16). Elucidation of the structure-property relationships of HEMs, particularly across different subcategories, is crucial to leverage the enhanced entropic effects for catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent papers have reviewed the catalytic applications mainly based on high-entropy alloys (HEAs), while entropy-stabilized systems beyond HEAs have been rarely covered (10)(11)(12)(13)(14)(15)(16). Elucidation of the structure-property relationships of HEMs, particularly across different subcategories, is crucial to leverage the enhanced entropic effects for catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Then, in 2018, Yao et al reported discrete HEA nanoparticles (NPs) . These demonstrations inspire study of synthetic pathways to nanostructured HEAs as their complex compositions and crystal size effects may together bring distinct functionality. ,, …”
Section: Introductionmentioning
confidence: 99%
“…High entropy alloys (HEAs) display distinct mechanical and functional properties. They are commonly defined as single-phase materials consisting of five or more elements in nearly equal amounts, where entropic stabilization accounts for compositionally complex solid solution formation. In 2004, Yeh et al reported nanostructured HEAs .…”
Section: Introductionmentioning
confidence: 99%
“…[19] iv) "Cocktail" effect refers to a kind of synergistic effect brought about by the interaction between various elements. [2,20] However, its specific physical meaning is not clear yet, and further explanation is needed from experiments and theory.…”
Section: Multi-sites Electrocatalysis In High-entropy Alloysmentioning
confidence: 99%